2021
DOI: 10.3389/fcimb.2021.771010
|View full text |Cite
|
Sign up to set email alerts
|

Codon Usage Bias in Autophagy-Related Gene 13 in Eukaryotes: Uncovering the Genetic Divergence by the Interplay Between Nucleotides and Codon Usages

Abstract: Synonymous codon usage bias is a universal characteristic of genomes across various organisms. Autophagy-related gene 13 (atg13) is one essential gene for autophagy initiation, yet the evolutionary trends of the atg13 gene at the usages of nucleotide and synonymous codon remains unexplored. According to phylogenetic analyses for the atg13 gene of 226 eukaryotic organisms at the nucleotide and amino acid levels, it is clear that their nucleotide usages exhibit more genetic information than their amino acid usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…In general, synonymous codon usage bias is able to participate in most aspects of viral life cycle. This biased synonymous codon usage is not neutral but involved in nucleotide usage bias ( 28 , 29 , 43 ), mRNA stability ( 44 , 45 ), translation accuracy and efficiency ( 46 , 47 ), and protein folding formation ( 48 ). Of note, BVDV did not follow nucleotide usage pattern of its susceptible host (i.e., newborn calf) in which the genome of cells contains high GC content to perform viral life cycle, but it accumulated adenine content in its ORF ( Supplementary Table 4 ) and suppressed the selection of synonymous codons with CG dinucleotides ( Supplementary Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, synonymous codon usage bias is able to participate in most aspects of viral life cycle. This biased synonymous codon usage is not neutral but involved in nucleotide usage bias ( 28 , 29 , 43 ), mRNA stability ( 44 , 45 ), translation accuracy and efficiency ( 46 , 47 ), and protein folding formation ( 48 ). Of note, BVDV did not follow nucleotide usage pattern of its susceptible host (i.e., newborn calf) in which the genome of cells contains high GC content to perform viral life cycle, but it accumulated adenine content in its ORF ( Supplementary Table 4 ) and suppressed the selection of synonymous codons with CG dinucleotides ( Supplementary Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, when the RSCU value is higher than 1.0, the corresponding synonymous codon displays a positive codon usage trend. In contrast, when the RSCU value is <1.0, the corresponding synonymous codon reflects a negative codon usage trend (28,29). To identify the extent of 59 synonymous codon usage bias, RSCU values of higher than 1.6 and <0.6 were defined as "overrepresented" and "underrepresented" codons, respectively (30).…”
Section: Analyzing Synonymous Codon Usage Patterns For the Bvdv Isolatesmentioning
confidence: 99%
“…By using a different analysis workflow, we revealed that the host factor, serving as one of the evolutionary dynamics, plays an important role in the genetic divergence of HEV derived from different hosts at synonymous codon usages. Synonymous codon usage bias, which can reflect the equilibrium between mutation pressure and natural selection, is a widespread genetic feature throughout the genomic evolution [33][34][35]. Although the HEV genome has a high mutation rate in its nucleotide sequence like other RNA viruses, the dispersion of the overall codon usage pattern of HEV displays the speciesspecific genetic feature.…”
Section: Discussionmentioning
confidence: 99%
“…Synonymous codon usage bias, which can reflect the equilibrium between mutation pressure and natural selection, is a widespread genetic feature throughout the genomic evolution [33–35]. Although the HEV genome has a high mutation rate in its nucleotide sequence like other RNA viruses, the dispersion of the overall codon usage pattern of HEV displays the species‐specific genetic feature.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the CUB of the ATG13 gene across eukaryotes has been reported [ 24 ]. However, the genetic pattern of the codon usage bias involved in human autophagy is not yet known.…”
Section: Introductionmentioning
confidence: 99%